МЕТОДИКА ОЦЕНКИ И СТРУКТУРА МИНЕРАЛЬНО-СЫРЬЕВОГО ПОТЕНЦИАЛА РЕГИОНА - Ешимбетов, У. (FAN va JAMIYAT, 2020)
The article is devoted to the study of methods and structure of economic evaluation of mineral resources. The structure of mineral-primary potential is transformed under the influence of changing external and internal factors. Innovative development gives opportunities to improve technics and technologies in reprocessing of mineral-primary resources.